Results of approbation of the innovative method of ion nitriding for steels with low temperatures of tempering - Andreev, A.; Sоbоl, O.; Shevchenko, S.; Stolbovoy, V.; Aleksandrov, V.; Kovteba, D.; Terletsky, A.; Protasenko, T. (PC тесhnology сеntеr, 2017)
The innovation technique of complex treatment for steels with the low temperature of tempering is proposed and tested in the course of present study. It includes nitriding in the vacuum gas discharge before hardening and tempering. In this case, during nitriding, the heating temperature influences little the process of high-temperature treatment. In this case, the process of diffusion of nitrogen atoms is accelerated considerably (since nitrogen atoms penetrate untempered steel more easily), which leads to an increase to 2000 µm in the depth of penetration of nitrogen atoms and in the thickness of the formed region with changed structure and hardness. It was established that, according to the properties, the region of exposure is divided into a surface layer (with a thickness of about 200 µm) with lowered hardness and the deeper operating layer with enhanced hardness. Layer with the greatest hardness is at depth of 400–800 µm. In this case, enhanced hardness, in comparison with the base, is maintained at depth that exceeds 2000 µm. The surface layer with low hardness makes it possible to implement the allowance for finishing, in order to obtain the required accuracy of dimensions and surface finish. Hardness of the surface of articles after this sequence of operations for the steels with low temperature of tempering is at the level of 8–10 GPa. The phase composition of the nitrided layer with high hardness, detected by the X-ray diffraction method, is the lowest nitride Fe4N and the solution of nitrogen in α-Fe.
Keywords: ionic nitriding; complex treatment; diffusion; depth of impact; diffraction spectra